Polimorfizmi dopaminskih receptorjev pri bolnikih s pigmentno retinopatijo - Rotar, Melita (Zdravniški vestnik, 2002)
Background. Dopamine (DA) has a specific role in modulation of retinal function, renewal and phagocytosis of shed discs by the retinal pigment epithelium. Animal model of RCS (Royal College of Surgeons) rats which have impaired retinal phagocytosis has shown an appearance similar to the clinical picture seen in patients with advanced retinitis pigmentosa (RP). Based on RCSrats' studies and the fact that DA has an important role in retinal renewalwe assume that certain DA receptor polymorphisms might play a role in pathogenesis of RP. Materials and methods. We compared a group of 65 RP patients and 80 healthy individuals. Using PCR method and restriction with Ddel, Taql or Mspl restriction enzymes (DRD1, DRD2, DRD3 respectively) we determined the polymorphisms of DRD1, DRD2 and DRD3. Three models of expression (codominant, dominant, recessive) were statistically compared with , chi2-test. Results. We found an evidence for association between DRD2 Taql RFLP, OR = 1.9 (95% CL: 1.7-2.3), p = 0.08, under autosome recessive model of inheritance. Other models for any of the DRD polymorphisms did not show a significant association with RP. Conclusions. A potential association was found between RP and DRD2 polymorphism. Further investigation is needed to confirm potential implication of DRD2 in the pathogenests of RP.
Keywords: dedne bolezni; fiziologija; Genotip; Genotype; oftalmologija; Polimeraza, verižna reakcija; Polimorfizem (genetika); Polymerase chain reaction; Polymorphism (genetics); Receptorji dopaminski; Receptors, dopamine; Retinitis pigmentosa; retinopatija